Compressive behaviour of slender FRP-confined concrete-encased cross-shaped steel columns. (20th October 2020) - Huang, Le; Yu, Tao; Wang, Zhen-Yu; Zhang, Shi-Shun
Highlights: A study on slender FRP-confined concrete-encased steel columns (FCCSCs) is presented. The test variables include column slenderness, load eccentricity and FRP thickness. The excellent structural performance of slender FCCSCs was demonstrated. The confinement effects are remarkable for slender FCCSCs under compression. Abstract: Fibre-reinforced polymer (FRP)-confined concrete-encased cross-shaped steel columns (FCCSCs) consist of a square FRP outer tube with round corners, a cross-shaped inner steel section and concrete filled in the between. The unique configuration of FCCSCs ensures that the concrete in the columns is well confined despite the square column shape, as demonstrated by the relevant existing research. The existing work on FCCSCs, however, has been limited to the behavior of short FCCSCs under axial compression. With their optimal configuration, the use of FCCSCs means that considerably reduced section dimensions may be adopted for the same load demand, leading to relatively slender columns in practice. In addition, the load eccentricity is an important parameter to consider in the column design. This paper presents the first-ever experimental study on the behaviour of slender FCCSCs. The test variables in this study included the load eccentricity, the slenderness ratio of the column and the thickness of FRP tube. The test results confirm the excellent structural performance of slender FCCSCs, and show that the load capacity of FCCSCs decreases with the slenderness ratio and the load eccentricity. Nevertheless, the confinement effects on the behavior of FCCSCs were found to be remarkable even when the column slenderness ratio and load eccentricity are large.